Symptom Experience Associated With Immunosuppressive Medications in Chinese Kidney Transplant Recipients. Issue 5 (28th July 2015) - Teng, Sha; Zhang, Shuping; Zhang, Wenxin; Lin, Xiaohong; Shang, Yabin; Peng, Xiao; Liu, Hongxia
Abstract: Purpose: Kidney transplant recipients require lifelong treatment with immunosuppressive medications to avoid graft rejection and graft loss. Symptoms experienced may influence recipients' perceived quality of life and medication adherence. The purpose of this study was to evaluate the symptom experience associated with immunosuppressive medications in adult kidney transplant recipients and to explore the association between the symptom experience and adherence to immunosuppressive medications. Design: A cross‐sectional design was used. The study was conducted in a general hospital in China from October 2013 to September 2014. A total of 231 recipients with a follow‐up of at least 1 year after kidney transplantation were included. Methods: Symptom experience associated with immunosuppressive medications was measured by the 13‐item Symptom Experience of Immunosuppressive‐related Side Effects Scale. Self‐reported adherence to immunosuppressive medications was assessed using the Adherence with Immunosuppressive Medication Scale. Ridit analysis was used to rank symptom distress items. Findings: A proportion of 60.6% of recipients were male; the time after kidney transplantation was arbitrarily divided into a short‐term cohort (1–4 years) and a long‐term cohort (4–16 years) according to the median duration of follow‐up (4 years). High blood pressure, hair loss, and tiredness were the three most distressing symptoms over all items of the whole sample. High blood pressure was the most distressing symptom for the 1‐ to 4‐year cohort and the 4‐ to 16‐year cohort. For men high blood pressure was the most distressing symptom, whereas for women hair loss was the most distressing symptom. Recipients in the 4‐ to 16‐year cohort perceived a higher level of symptom distress compared with those in the 1‐ to 4‐year cohort, especially in excess hair growth and difficulty sleeping. A negative relationship was found between symptom distress and adherence to immunosuppressive medications (r = ‐.541, p = .000). Conclusions: Recipients in the 4‐ to 16‐year cohort perceived a higher level of symptom distress compared with those in the 1‐ to 4‐year cohort, especially in excess hair growth and difficulty sleeping. No significant difference was found between gender groups. Recipients who reported a higher level of symptom distress were more likely to be nonadherent. Clinical Relevance: Understanding symptom experience of immunosuppressive medications is of importance for healthcare providers to offer sophisticated education and develop strategies to improve quality of life and medication adherence during follow‐up post‐transplantation.